Principles of Civil And Sharia Civil Law In The Implementation of Wakaf - Achmad Rafi Resaf Pratama; Rusdianto Sesung (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2023)
Waqf is the legal act of a wakif to separate and/or hand over part of his property to be used forever or for a certain period of time in accordance with his interests for the purposes of worship and/or general welfare according to sharia. In reality, not all waqf givers understand the concept of waqf in general, this can be seen in a legal case that was decided in Civil Case Lawsuit No. 230/Pdt.G/2018/PTA.Smg. That this research aims to analyze more deeply about waqf and analyze waqf legal cases as in Civil Case Lawsuit No. 230/Pdt.G/2018/PTA.Smg. The research method in this legal research uses normative juridical methods using several approaches to make analysis easier. The formulation of the problem used in this research is the principles of civil law and civil sharia in the implementation of waqf and the application of the principles of civil law and civil sharia in the civil case lawsuit No. 230/Pdt.G/2018/Pta.Smg. The conclusion from this research is that Waqf is the legal act of a wakif to separate and/or hand over part of his property to be used forever or for a certain period of time in accordance with his interests for the purposes of worship and/or general welfare according to sharia. Inimplementation waqf, it is obligatory to follow Islamic sharia and laws and regulations regarding waqf, so that the waqf is valid in accordance with the sharia and applicable laws. That property that has been donated cannot be canceled unilaterally by the wakif, therefore it is obligatory in implementing the waqf to carry out the terms and conditions as stated in the waqf terms and laws. It is best that before implementing the waqf pledge, Nadzir should assess the economic capabilities of the wakif so that there will be no incidents like in the civil case and avoid lawsuits for canceling the waqf pledge deed.